Human Rights in Contemporary Islamic political thought (قضايا سياسية, 2024)
This research aims to clarify the general concepts of human rights in contemporary Islamic political thought without delving into their detailed jurisprudential dimensions, as the primary goal is to explore the intellectual aspects. It relies on thinkers regardless of their sectarian or partisan affiliations, focusing on the doctrinal dimension from which the thinker derives their analytical vision regarding the dimensions of human rights in Islam.       The aim of Islam is to establish an ideal moral system grounded in society, were Islamic doctrine includes universal principles that are meant to be eternal and applicable in all times and places, supported by a just and sound legal framework governing human behavior in various actions and dealings, concerning oneself and in relation to one’s family and society, as well as with other communities and nations. It is important to note that the fundamental goal of Islam is to reform the individual aspect of a person. Undoubtedly, a significant portion of Islamic principles can only be implemented through interpersonal interactions and collective efforts, resulting in the proper application of Islamic principles and benefiting from them in the best possible way.